2018
DOI: 10.1186/s12977-018-0458-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of inflammation and T cell activation after 6 months of cART initiation during acute, but not in early chronic HIV-1 infection

Abstract: ObjectivesTo investigate the impact of early combined antiretroviral therapy (cART) on inflammation biomarkers and immune activation during acute and early chronic HIV-1 infection.MethodsWe included 12 acute (AHI), 11 early chronic (EcHI), and 18 late chronic HIV-1-infected (LcHI) individuals who were treated with cART and 18 HIV-1-uninfected (HIV-neg) individuals. Plasmatic levels of inflammation biomarkers, CD8+CD38+HLA-DR+ T cell frequencies, CD4 T cell counts, CD4/CD8 ratio, total HIV-1 DNA and plasmatic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 58 publications
5
21
0
5
Order By: Relevance
“…Chronic, treated HIV infection, in which viral load is control by antiretroviral therapy, is also accompanied by immune dysregulation despite control of viremia and improvement in CD4+ T cell counts. Elevated levels of activated CD4+ and CD8+ T cells, marked by expression of activation markers such as HLA-DR, have been reported in HIV-positive patients receiving cART, although levels of inflammatory cytokines and the numbers of activated cells decrease with initiation of therapy, particularly if therapy is initiate early during acute infection (143,144). Depletion of naïve CD4+ T cells in patients on long term cART was also reported (145,146).…”
Section: T Lymphocyte Dysfunction In Acute and Chronic Hiv Infectionmentioning
confidence: 95%
“…Chronic, treated HIV infection, in which viral load is control by antiretroviral therapy, is also accompanied by immune dysregulation despite control of viremia and improvement in CD4+ T cell counts. Elevated levels of activated CD4+ and CD8+ T cells, marked by expression of activation markers such as HLA-DR, have been reported in HIV-positive patients receiving cART, although levels of inflammatory cytokines and the numbers of activated cells decrease with initiation of therapy, particularly if therapy is initiate early during acute infection (143,144). Depletion of naïve CD4+ T cells in patients on long term cART was also reported (145,146).…”
Section: T Lymphocyte Dysfunction In Acute and Chronic Hiv Infectionmentioning
confidence: 95%
“…The timing of ART start is known to affect virological and immunological outcomes in HIV-infection: indeed, early treatment is associated with improved virus control and reduced levels of cellular virus reservoir [63,64]. One recent study by De Paula et al showed that in HIV-infected adult patients, plasma levels of inflammatory biomarkers (IP-10, IL-18, sCD163) and CD8+CD38+HLA-DR+ T cell frequencies were significantly reduced after six months of ART in early-treated but not in late-treated individuals [65]. Furthermore, Allers et al showed that in patients who initiated ART during acute HIV infection, mucosal CD4+ T cell numbers were well preserved, and markers of microbial translocation and inflammation reversed to normal [66].…”
Section: Initiation and Duration Of Art Can Affect Chronic Immune mentioning
confidence: 99%
“…To understand the potential impact of the SI on the host immune system, we analyzed alterations during the follow-up period in the frequencies of the T cell subsets and immune response to HIV peptides in PBMC samples collected at V3 2010 (prior to SI), V4 2011 (at the moment of B2 env variant identification after SI onset), V7 2013 (prior to the first peak of viremia), V9 2014 (at the first peak of viremia and detection of B 1 and B 2 env and int variants), V14 2016 (after viremia control) and V16 2017 (at the second peak of viremia). Briefly, T cell activation was evaluated by multiparametric flow cytometry by staining the cells with anti-CD3, anti-CD4 or anti-CD8, anti-CD38 and anti-HLA-DR antibodies to determine the frequencies of CD38 + HLA-DR + cells in both CD4 + and CD8 + subsets, as previously described [22]. In addition, cells were also labeled with anti-CD45RA, anti-CD27 and anti-CD95 antibodies to evaluate the frequencies of naïve (TN; CD45RA + CD27 + CD95 − ), system memory (TSCM; CD45RA + CD27 + CD95 + ), central memory (TCM; CD45RA − CD27 + CD95 + ), effector memory (TEM; CD45RA − CD27 − CD95 + ) and effector (TEFF; CD45RA + CD27 − CD95 + ) T cell subsets.…”
Section: Case Presentationmentioning
confidence: 99%